Wpływ chrztu Polski na język ojczysty - Ożóg, Kazimierz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Chrzest Polski w X wieku to dla języka polskiego i ojczystej kultury akt historyczny. Akt ten miał fundamentalny wpływ na kształtowanie się języka polskiego. Przez akt chrztu i następujące po nim dzieło chrystianizacji w obrządku łacińskim język polski przeszedł z ery mowy do ery pisma i uzyskał dostęp do kultury Zachodu. Alfabet łaciński wprowadzał stopniowo polszczyznę do grona literackich języków europejskich. Pod wpływem chrztu ukształtowała się nowa leksyka wyrażająca podstawy wszystkich nauk, zręby edukacji, leksyka religijna, moralna, zostały utworzone piękne imiona osób. Biblia, tłumaczona na język polski, od co najmniej 700 lat stała się wzorem tekstów literackich.

Baptism of Poland in the 10th century is a historical act for the Polish language and native culture. This act had a fundamental impact on the formation of the Polish language. Through the act of baptism and the subsequent work of Christianization in the Latin rite, the Polish language passed from the era of speech to the era of writing and gained access to Western culture. The Latin alphabet gradually introduced Polish to the group of literary European languages. Under the influence of baptism, a new lexicon was formed expressing the foundations of all sciences, the foundations of education, religious and moral lexis, beautiful names of people were created. The Bible, which has been translated into Polish for at least 700 years, has become a model of literary texts.
The Influence of Polish Baptism on the Native Language
Keywords: chrzest Polski; era pisma; alfabet łaciński; kultura; Baptism of Poland; era of writing; Latin alphabet; culture